Effects of immunosuppressive treatment on protein expression in rat kidney - Kędzierska, Karolina (Dove Medical Press, 2014)
The structural proteins of renal tubular epithelial cells may become a target for the toxic metabolites of immunosuppressants. These metabolites can modify the properties of the proteins, thereby affecting cell function, which is a possible explanation for the mechanism of immunosuppressive agents’ toxicity. In our study, we evaluated the effect of two immunosuppressive strategies on protein expression in the kidneys of Wistar rats. Fragments of the rat kidneys were homogenized after cooling in liquid nitrogen and then dissolved in lysis buffer. The protein concentration in the samples was determined using a protein assay kit, and the proteins were separated by two-dimensional electrophoresis. The obtained gels were then stained with Coomassie Brilliant Blue, and their images were analyzed to evaluate differences in protein expression. Identification of selected proteins was then performed using mass spectrometry. We found that the immunosuppressive drugs used in popular regimens induce a series of changes in protein expression in target organs. The expression of proteins involved in drug, glucose, amino acid, and lipid metabolism was pronounced. However, to a lesser extent, we also observed changes in nuclear, structural, and transport proteins’ synthesis. Very slight differences were observed between the group receiving cyclosporine, mycophenolate mofetil, and glucocorticoids (CMG) and the control group. In contrast, compared to the control group, animals receiving tacrolimus, mycophenolate mofetil, and glucocorticoids (TMG) exhibited higher expression of proteins responsible for renal drug metabolism and lower expression levels of cytoplasmic actin and the major urinary protein. In the TMG group, we observed higher expression of proteins responsible for drug metabolism and a decrease in the expression of respiratory chain enzymes (thioredoxin-2) and markers of distal renal tubular damage (heart fatty acid-binding protein) compared to expression in the CMG group. The consequences of the reported changes in protein expression require further study.